Identifying Clinically Relevant Drug–Drug Interactions With Methadone and Buprenorphine: A Translational Approach to Signal Detection. Issue 5 (20th August 2022) - Miano, Todd A.; Wang, Lei; Leonard, Charles E.; Brensinger, Colleen M.; Acton, Emily K.; Dawwas, Ghadeer K.; Bilker, Warren B.; Soprano, Samantha E.; Nguyen, Thanh Phuong Pham; Woody, George; Yu, Elmer; Neuman, Mark; et al.
Abstract : Methadone and buprenorphine have pharmacologic properties that are concerning for a high risk of drug–drug interactions (DDIs). We performed high‐throughput screening for clinically relevant DDIs with methadone or buprenorphine by combining pharmacoepidemiologic and pharmacokinetic approaches. We conducted pharmacoepidemiologic screening via a series of self‐controlled case series studies (SCCS) in Optum claims data from 2000 to 2019. We included persons 18 years or older who experienced an outcome of interest during target drug treatment. Exposures were all overlapping medications (i.e., the candidate precipitants) during target drug treatment. Outcomes were opioid overdose, non‐overdose adverse effects, and cardiac arrest. We used conditional Poisson regression to calculate rate ratios, accounting for multiple comparisons with semi‐Bayes shrinkage. We explored the impact of key study design choices in analyses that varied the exposure definitions of the target drugs and the candidate precipitant drugs. Pharmacokinetic screening was conducted by incorporating published data on CYP enzyme metabolism into an equation‐based static model. In SCCS analysis, 1, 432 events were included from 248, 069 new users of methadone or buprenorphine. In the primary analysis, statistically significant DDIs included gabapentinoids with either methadone or buprenorphine; baclofen with methadone; and benzodiazepines with methadone. In sensitivity analysis, additional statistically significant DDIs included methocarbamol, quetiapine, or simvastatin with methadone. Pharmacokinetic screening identified two moderate‐to‐strong potential DDIs (clonidine and fluconazole with buprenorphine). The combination of clonidine and buprenorphine was also associated with a significantly increased risk of opioid overdose in pharmacoepidemiologic screening. These DDI signals may be the most important targets for future confirmation studies.